Impact evaluation and economic benefit analysis of a domestic violence and abuse UK police intervention - Karavias, Yiannis; Bandyopadhyay, Siddhartha; Christie, Christine; Bradbury-Jones, Caroline; Taylor, Julie; Kane, Eddie; Flowe, Heather D. (Frontiers in Psychology, 2023)
This study evaluated the impact and economic benefit of CARA (Cautioning and Relationship Abuse), an intervention which aims to reduce reoffending of first-time low-level domestic violence and abuse perpetrators. The analysis was based on two samples drawn from separate UK police force areas. CARA’s impact was assessed using a matched sample of similar offenders from a time when CARA was not available. The matching was based on a host of offender and victim characteristics and machine learning methods were employed. The results showed that the CARA intervention has a significant impact on the amount of recidivism but no significant reduction in the severity of the crimes. The benefit-cost ratio in both police force areas is greater than one and estimated to be 2.75 and 11.1, respectively across the two police force areas. Thus, for each pound (£) invested in CARA, there is an economic benefit of 2.75-11.1 pounds, annually.